The stratigraphic and structural controls on copper-gold mineralization at Cassenha hill prospect, within the Archean to Paleoproterozoic Angolan shield, Congo craton, South Western Angola - vaz Sidre, Stelvio (Department of Geological Sciences, 2021)
The Cassenha Hill copper-gold prospect is situated in the Catabola area, Huambo Province, southwestern Angola. Geologically, the prospect is part of the Angolan Central Eburnean Zone (CEZ) and consists of Paleoproterozoic metasedimentary rock sequences which have been intruded by Eburnean granitoids at ± 2.1 Ga. The prospect itself comprises an area of 180 Km2 and has been intermittently explored since 2005 by Rift Valley Resources (RVR) and its associates. The Cassenha Hill prospect is characterized by the occurrence of partially altered and highly oxidized metasedimentary rocks (meta-mudstone, meta-siltstone, carbonate-rich rock, meta-sandstone, breccia, and quartzite), and altered isolated granitoids. This study represents the first detailed study of the prospect and aims to shed light on the characteristics of the various rock types (i.e., host and barren rocks), their source/provenance, styles of alteration, and the origin and/or type of the fluid responsible for the mineralization. Techniques applied include borehole core logging, petrography, whole-rock geochemistry (XRF and ICP-MS), and stable isotope geochemistry on samples collected on the surface and from exploration boreholes drilled as part of RVR exploration program. Overall, the petrographic and geochemical studies undertaken in the rocks of the Cassenha Hill prospect indicate the following: (1) The rocks are moderately to strongly fractured; (2) The rocks have experienced weak to moderate chemical weathering; (3) The rocks are compositionally immature and originated from felsic provenance; (4) The rocks are sulfur-poor, and lacking in sulfide minerals (5) The rocks are enriched in LREE and LILE elements and depleted in HREE and HFSE elements; (6) The mineralization is associated with chloritization alteration and predominantly occurs within and/or at the edges of quartz/chlorite-rich veins/fractures and is not restricted to any rock type. Two ore stages could be identified, namely, hypogene ore (stage I) consisting of pyrite ± chalcopyrite ± other copper sulfides, and supergene ore (stage II) consisting of malachite ± azurite ± chrysocolla, which represents the prevalent mineralization at the prospect. The δ 18O value of quartz veins range from +12.81 to +13.53‰, while the δD of chlorite minerals range from -51 to -45‰. Therefore, assuming fluid-rock interaction took place at ≈ 350oC, due to the presence of quartz, the fluid had δ 18OH20 values of about +8‰, which are typical of magmatic waters. On the other hand, at a temperature of ≈ 350oC, and with the difference between chlorite and water being -33.5‰, such fluids would have had δDH20 values of about -20‰ (δ 18OH20= -4‰), which are typical of meteoric waters. Although the various mineral phases have yielded different isotopic signatures, this study suggests that water is ultimately of meteoric origin but exchanged with hydrogen-poor magmatic rock, thus maintaining the meteoric signature. The continuous influx of meteoric waters within the fracture system led to the development of copper oxides such as malachite, azurite and chrysocolla, which possibly originated from the insitu oxidation of the hypogene sulfides. This signature, together with other field, petrographic and geochemical observations allows one to, tentatively, suggest that the Cassenha Hill prospect represents an extension of a polymetallic vein-type of porphyry Cu deposit that has been subjected to supergene processes at the weathering profile.